DNS root domain name analysis system based on block chain - Tianshu ZHUANG; Wenfeng LIU; Dong LI (Dianxin kexue)
The centralized resolution system of the domain name system (DNS) implies an unavoidable risk of abuse of power,a top-level domain may be deleted from the root zone.By analyzing the related work on the root zone decentralization,the most were mainly to deploy new root resolution services outside the current root servers,but not to decentralize the root zone data.A scheme to decentralize the root zone data was proposed,and the decentralization of root zone data distribution and analysis were achieved through a peer-to-peer coalition between national roots.Trust from peer-to-peer to collective,with features such as autonomy,openness,equality,and transparency,and implements a distributed consensus on root zone data through blockchain technology were transformed by the program,thereby ensuring root zone data consistency.